Standardization of 123I-metaiodobenzylguanidine cardiac neurotropic scintigraphy and single-photon emission tomography - A. A. Ansheles; V. B. Sergienko (Вестник рентгенологии и радиологии)
Current review describes the prerequisites for clinical application of nuclear imaging with metaiodobenzylguanidine for cardiac sympathetic activity assessment. As the method developed, various quantitative parameters were proposed to evaluate its results. Some of them are still calculated and interpreted differently in various medical centers. This review systemizes the data regarding the attempts of method standardization, and describes factors that inhibit its validation for clinical trials.